بعين الناظر: صحة الفم المرتبطة بنوعية الحياة عند الأطفال المصابين بالأذيات الرضية السنية خلال الأزمة السورية - دشاش, ميسون; الموصللي, هبة (Latakia University Journal -Medical Sciences Series, 2017)
Objective: Health care providers in emergency settings encounter emotional issues in treating traumatic dental injuries TDIs which may have a significant negative impact on the quality of life. Assessing OHRQoL of children with TDIs, in emergency, promote a shift from traditional dental management to a more supportive care that focuses on a person’s social and emotional status and physical functioning in which appropriate health care and optimal outcomes can be obtained. The objective of this study is to investigate the impact of TDIs on the quality of life of 7to16-year-old Syrian school children and to test whether treatment of TDI will improve their OHRQoL. Basic research design:A case-control study was carried out involving 147children aged 7 to 16 years attending the Department of Pediatric Dentistry in Damascus University. Andreasen classification was adopted for TDI diagnosis. CPQ11-14 instrument was utilized to assess OHRQoL.Results: Findings of this study revealed significant differences in OHRQoL items before and after treatment of participating children. There were no statistically significant differences between healthy children and those who were treated with TDI in regard to the overall OHRQoL (P > 0.05). Conclusions: OHRQoL was significantly improved in children with TDIs after treatment. Oral symptoms, functional limitations, emotional and social well-being were similar to healthy children. Health professionals in Syria should put efforts to make war less damaging for children and their parents. Dentistry during the crisis goes beyond filling and drilling of injured teeth to a moral commitment within a supportive and caring context.الهدف: يصادف مقدمو الرعاية الصحية في قسم الإسعاف أموراً عاطفية التي من شأنها أن تعكس تأثيراً سلبياً على نوعية الحياة أثناء معالجة الأذيات الرضية السنية. وإنّ تقييم صحة الفم المرتبطة بنوعية الحياة أثناء المعالجة وتدبير الأذيات الرضية السنية في الحالات الإسعافية يعزز ويحول عملية التدبير من سنية تقليدية إلى رعاية داعمة تركز على الحالات الاجتماعية والعاطفية والجسدية للفرد، بحيث يتم تحقيق رعاية صحية مناسبة ونتائج مثالية. كان الهدف من هذه الدراسة تحري تأثير الأذيات الرضية السنية علىنوعية الحياة لدى أطفال المدارس السوريين بين عمري 7-16عاماً واختبار ما إذا كان معالجة هذه الأذيات يحسن من صحة الفم المرتبطة بنوعية الحياة.التصميم الأساسي للبحث:أجريت دراسة حالة-شاهد بمشاركة 147 طفلاً بين عمري 7-16 عاماً من المراجعين لقسم طب أسنان الأطفال في جامعة دمشق. تم اعتماد تصنيف Andreasen لتشخيص الأذيات الرضية السنية. وتم استخدام استبيان إدراك الطفل CPQ11-14 لتقييم صحة الفم المرتبطة بنوعية الحياة(P > 0.05).الخلاصة:تحسنت صحة الفم المرتبطة بنوعية الحياة بشكل واضح عند الأطفال المصابين بالأذيات الرضية السنية بعد المعالجة. وكانت الأعراض الفموية والقصور الوظيفي والحالتين العاطفية والاجتماعية جميعها مشابهة لتلك الموجودة عند الأطفال الأصحاء. لذا يتوجب على اختصاصي الصحة في سوريا بذل المزيد من الجهود لتخفيف وطأة وأثر الحرب على الأطفال وذويهم. وعلى طب الأسنان في الأزمات أن يتجاوز تحضير وترميم السن المصابة إلى التزامات أخرى أخلاقية تشمل من خلالها مفهومي الرعاية والدعم معاً.